Pengaruh Waktu Perebusan Biji Nangka (Artocapus heterophyllus Lamk) Terhadap Kadar Karbohidrat, Protein, Dan Lemak - Yulianti, Selvi; Ratman, Ratman; Solfarina, Solfarina (Universitas Tadulako, 2015)
Jackfruit seeds are part of the jackfruit which were not used optimally. The seeds can be eat directly after boiling and can also be changed as flour because it contains carbohydrates, proteins, and fats. This study was conducted to test the levels of carbohydrates, proteins, and fats of jackfruit seeds after boiled at different times, which were 15 minutes, 30 minutes, and 45 minutes. Carbohydrates, proteins, and fats were determined successively using the phenol sulfuric acid, the kjeldahl and the soxhlet extraction methods. Levels of carbohydrates at various boiling times of 15 minutes, 30 minutes, and 45 minutes were 49.06%, 43.68%, dan 42.75%. Levels of proteins were 3.928%, 3.84%, and 3.57%, while levels of fats were 5.40%, 0.95%, and 0.40%. The results showed that the longer the boiling time affected to declining levels of carbohydrates, proteins, and fats.